Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1038/nature20162
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and mechanistic diversity of piRNA 3′-end formation

Abstract: Small regulatory RNAs guide Argonaute (Ago) proteins in a sequence-specific manner to their targets and thereby play important roles in eukaryotic gene silencing1. Of the three small RNA classes, microRNAs and siRNAs are processed from double-stranded precursors into defined 21- to 23-mers by Dicer, an endoribonuclease with intrinsic ruler function. piRNAs—the 22-30 nt long guides for PIWI-clade Ago proteins that silence transposons in animal gonads—are generated Dicer-independently from single-stranded precur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
175
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(191 citation statements)
references
References 39 publications
11
175
1
4
Order By: Relevance
“…3’ end formation can also be induced by slicer (ping-pong) cleavage. In this case, the mature piRNA is generated by two closely spaced slicer cleavages [77]. Finally, 3’ end formation might require processing by exonuclease(s).…”
Section: Pirna Biogenesis In the Cytoplasmmentioning
confidence: 99%
See 2 more Smart Citations
“…3’ end formation can also be induced by slicer (ping-pong) cleavage. In this case, the mature piRNA is generated by two closely spaced slicer cleavages [77]. Finally, 3’ end formation might require processing by exonuclease(s).…”
Section: Pirna Biogenesis In the Cytoplasmmentioning
confidence: 99%
“…In this case, a 3’-to-5’ exonuclease trims a longer precursor formed by cleavage by an endonuclease (slicer or Zuc) to make mature piRNAs of the correct size. Such ‘Trimmer’ activity was first observed in vitro using lysate from a silkworm cell line [78] and later associated with the exonuclease Nibbler (Nbr) [77, 79, 80]. Independently of the mechanism by which the 3’end of piRNAs is generated, the last step is the 2’OMe-modification of the last nucleotide by Hen1, which is thought to increase the stability of piRNAs [8082].…”
Section: Pirna Biogenesis In the Cytoplasmmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was isolated with TRIzol reagent according to the manufacturer's instructions, and 2S rRNA was depleted as described (Hayashi et al, 2016). Small RNA libraries were generated as described (Jayaprakash et al, 2011).…”
Section: Small Rna-seqmentioning
confidence: 99%
“…Recently, it was shown that high expression of piwi-like protein 4 in leukemic cells in 72% of the patients with different types of AML compared to healthy controls, and in 90% of the patients with MLL-AF9 rearranged AML [13,65]. PiRNAs act as sequence-specific guides for piwi proteins, and they support biogenesis and stability of piRNAs.…”
Section: Piwi-interacting Rnasmentioning
confidence: 99%